2020
DOI: 10.1016/j.bjps.2020.08.044
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and safety of immediate breast reconstruction in the COVID-19 era

Abstract: The coronavirus disease-2019 pandemic has had a significant impact on the delivery of surgical services, particularly reconstructive surgery. This article examines the current evidence to assess the feasibility of recommencing immediate breast reconstruction services during the pandemic and highlights considerations required to ensure patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Jallali et al, while asserting that IBR should continue to be recommended, also identified patients with certain comorbidities (BMI > 35 kg/m 2 , diabetes, and chronic cardiac or respiratory disease) who should instead undergo a delayed reconstruction. 24 Further, in the current analysis, we are unable to directly quantify the impact of the added procedure on resource utilization. Mastectomy with immediate reconstruction involves 2 operating teams, greater utilization of PPE, and longer operative times, which decrease the availability of free anesthesiologists and ventilators.…”
Section: Discussionmentioning
confidence: 92%
“…Jallali et al, while asserting that IBR should continue to be recommended, also identified patients with certain comorbidities (BMI > 35 kg/m 2 , diabetes, and chronic cardiac or respiratory disease) who should instead undergo a delayed reconstruction. 24 Further, in the current analysis, we are unable to directly quantify the impact of the added procedure on resource utilization. Mastectomy with immediate reconstruction involves 2 operating teams, greater utilization of PPE, and longer operative times, which decrease the availability of free anesthesiologists and ventilators.…”
Section: Discussionmentioning
confidence: 92%
“…For several months breast reconstruction services were halted. We published guidance on restarting immediate abdominal based reconstructive surgery following mastectomy in the breast cancer setting 1 . This included details of patient selection, COVID-19 testing, and recommended in-patient and out-patient follow-up protocols.…”
mentioning
confidence: 99%
“…During the pandemic, evidence suggested that age over 65 and BMI over 35 increased the risk of severe COVID-related illness 1 . In terms of co-morbidities, our COVID-19 pathway meant that we could no longer offer the surgery to patients with diabetes, those over the age of 70, those with a BMI greater than 35.0, and those with chronic cardiac, respiratory or renal disease.…”
mentioning
confidence: 99%
“…While the current COVID-19 pandemic appears to be resolving, it is likely that further pandemics, with third and even fourth waves can occur over the coming months and potentially years. Hence, it is imperative that robust protocols are now conceived, to avoid undue delay in decision-making in the future [ 7 ].…”
mentioning
confidence: 99%